Patient safety with covid-19 in hospital units: a scoping review - Fernanda de Macedo Coelho Leite; Eloysa dos Santos Oliveira; Bruna Vilar Soares da Silva; Evelin Beatriz Bezerra de Melo; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: Map, in the scientific literature, the actions taken to promote the safety of patients with covid-19 in the hospital context. Methods: This is a scoping review according to the Joanna Briggs Institute, using the Checklist Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. In April 2022, searches were performed on nine data sources. The results were summarized in a table and analyzed descriptively. Results: Fifteen studies were selected to compose the final sample. Most articles refer to cohort studies, followed by clinical trials. As for the areas of activity, there was a predominance of surgical centers, followed by adult and pediatric Intensive Care Units. Conclusions: With this review, it was possible to map measures such as contingency plans and reorganization of beds, rooms, and operating rooms, in addition to the isolation and distancing practiced by patients and professionals.